2004
DOI: 10.1007/bf03040482
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethylstärke (HES)

Abstract: Adequate volume replacement therapy is a mainstay of managing the critically ill. The ideal kind of volume replacement in this situation still remains a challenge. In spite of an immense number of contributions to this problem there is still no definite answer. The ideal volume replacement strategy should not only aim at maintaining stable systemic hemodynamics, organ perfusion and microcirculation should be guaranteed or even improved as well. Due to its excellent efficacy, hydroxyethylstarch (HES) preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…When the results of the Schortgen study appeared, which found increased ARF after HES 200/0.6 in septic patients, this was explained as a consequence of using "highly substituted HES 200/0.6" while 10% HES 200/0.5 was at the same time regarded as "a modern HES solution" with "no negative eff ect … on renal function" based on the results of the 1998 study [47]. Elsewhere, 10% HES 200/0.5 was claimed to be a "modern HES solution of medium molecular weight and medium degree of substitution" and to be "harmless in the therapy of sepsis" [15].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…When the results of the Schortgen study appeared, which found increased ARF after HES 200/0.6 in septic patients, this was explained as a consequence of using "highly substituted HES 200/0.6" while 10% HES 200/0.5 was at the same time regarded as "a modern HES solution" with "no negative eff ect … on renal function" based on the results of the 1998 study [47]. Elsewhere, 10% HES 200/0.5 was claimed to be a "modern HES solution of medium molecular weight and medium degree of substitution" and to be "harmless in the therapy of sepsis" [15].…”
Section: Discussionmentioning
confidence: 92%
“…Elsewhere, 10% HES 200/0.5 was claimed to be a "modern HES solution of medium molecular weight and medium degree of substitution" and to be "harmless in the therapy of sepsis" [15]. "Especially in patients with total renal insuffi ciency, care should be taken to use easily degradable HES solutions with a low degree of substitution (0.4 or 0.5)" [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boldt [10] has recently argued that the safety problems of HES can be ignored, as long as clinicians use "modern" solutions such as HES 200/0.5 and HES 130/ 0.4. This contention needs to be critically appraised.…”
Section: Introductionmentioning
confidence: 99%